2009
DOI: 10.1094/pdis-93-12-1298
|View full text |Cite
|
Sign up to set email alerts
|

New Genotypes of Fusarium oxysporum f. sp. vasinfectum from the Southeastern United States

Abstract: Sixty-one isolates of Fusarium oxysporum f. sp. vasinfectum were collected from cotton plants (Gossypium spp.) with symptoms of Fusarium wilt to determine the composition of races present in the southeastern United States. Analysis of partial sequences of the translation elongation factor gene revealed four novel genotypes, as well as the presence of races 3 and 8 for the first time in the United States outside of California. The majority of isolates (16 of 27) sampled from Arkansas were novel genotypes. A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…There are currently eight races recognized worldwide, including races 1, 2, 3, 4, and 8 in the United States (Holmes, Bennett, Spurgeon, Colyer, & Davis, ; Kim, Hutmacher, & Davis, ); race 3 in Egypt and Israel; race 4 in India; race 5 in Sudan; race 6 in Brazil; and races 7 and 8 in China (Sanogo & Zhang, ). In the last 15 yr, the yield loss in California caused by FOV race 4 (FOV4) has increased (Hutmacher et al., ) since it was first reported in the state in 2001 (Holmes et al., ; Kim et al., ). This race has been spread eastward to other western and southwestern cotton states, including far‐western Texas (El Paso County), based on field scouting followed by molecular confirmation (Halpern et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…There are currently eight races recognized worldwide, including races 1, 2, 3, 4, and 8 in the United States (Holmes, Bennett, Spurgeon, Colyer, & Davis, ; Kim, Hutmacher, & Davis, ); race 3 in Egypt and Israel; race 4 in India; race 5 in Sudan; race 6 in Brazil; and races 7 and 8 in China (Sanogo & Zhang, ). In the last 15 yr, the yield loss in California caused by FOV race 4 (FOV4) has increased (Hutmacher et al., ) since it was first reported in the state in 2001 (Holmes et al., ; Kim et al., ). This race has been spread eastward to other western and southwestern cotton states, including far‐western Texas (El Paso County), based on field scouting followed by molecular confirmation (Halpern et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, analyses with partial sequences from the above genes of 61 FOV isolates across the United States (Holmes et al, 2009) revealed four additional FOV genotypes, and for the first time, Races 3 and 8 were reported outside of California. The majority of these novel genotypes were from the state of Arkansas and were pathogenic to at least one cotton cultivar used in the study (Holmes et al, 2009).…”
mentioning
confidence: 99%
“…In the United States, races 1, 2, 3, 4, and 8 were identified (Cianchetta et al., ; Holmes, Bennett, Spurgeon, Colyer, & Davis, ; Kim, Hutmacher, & Davis, ). Race 4 (FOV4) was originally identified in India and has become a major threat to US cotton production (Halpern et al., ; Hutmacher et al., ; Zhu et al., ) since it was first reported in California in 2001 (Holmes et al., ; Kim et al., ). Other races are recognized in other cotton‐producing countries, including race 3 in Egypt and Israel, race 5 in Sudan, race 6 in Brazil, and races 7 and 8 in China (Hillocks, ; Sanogo & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium wilt is one of the diseases most destructive to the development of cotton. In the United States, races 1, 2, 3, 4, and 8 were identified (Cianchetta et al, 2015;Holmes, Bennett, Spurgeon, Colyer, & Davis, 2009;Kim, Hutmacher, & Davis, 2005). Race 4 (FOV4) was originally identified in India and cultivars.…”
Section: Introductionmentioning
confidence: 99%